Education of Pancasila Values to Strengthen Villages' Awareness of Harmony in Pacet Village, Mojokerto Regency, East Java - Listyaningsih, Listyaningsih; Warsono, Warsono; Setyowati, Raden Roro Nanik; Sari, Maya Mustika Kartika; Adi, Agus Satmoko; Huda, Mi'rojul; Usmi, Rianda; Thohari, Habib Nihla; Chamidah, Nur (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
In facing national problems such as intolerance and ethnic and social conflicts, Indonesia needs to re-actualize the values of Pancasila, which have been proven as a unifying solution for the nation. Pancasila, as the foundation of the state and the nation's outlook on life, plays an important role in uniting the ethnic, religious, and cultural differences in Indonesia. However, in daily practice, the values of Pancasila tend to be eroded and are more present as formal symbols than behavioral guidelines, thus triggering various disputes between residents. Therefore, the purpose of this community service activity Pancasila is intended to (1) instill Pancasila values in the Pacet Village community; (2) mentor the Pacet Village youth organization as a facilitator of harmony by utilizing social media to campaign for harmony in society. This community service activity is a collaboration between the Pancasila and Citizenship Education Study Program, Surabaya State University with the Pacet Village Government, Pacet District, Mojokerto Regency, and the Mojokerto Regency Interfaith Harmony Forum. This community service activity is a Pancasila Discussion and Creative Content Creation Training for Karang Taruna Pacet Village. The method used is socialization, which provides material about Pancasila as a unifier of the nation, ending with digital content training. Through socialization activities, national insight training, discussions with religious leaders, and training for village officials, efforts to strengthen Pancasila encourage a harmonious life amidst diversity.